2014
DOI: 10.3389/fnhum.2014.00568
|View full text |Cite
|
Sign up to set email alerts
|

The influence of expertise on brain activation of the action observation network during anticipation of tennis and volleyball serves

Abstract: In many daily activities, and especially in sport, it is necessary to predict the effects of others' actions in order to initiate appropriate responses. Recently, researchers have suggested that the action–observation network (AON) including the cerebellum plays an essential role during such anticipation, particularly in sport expert performers. In the present study, we examined the influence of task-specific expertise on the AON by investigating differences between two expert groups trained in different sport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 83 publications
(145 reference statements)
9
49
0
2
Order By: Relevance
“…Cross-sectional studies comparing groups with different expertise levels have revealed that expertise is associated with beneficial functional brain network characteristics [25, 34, 35, 37]. In line with these findings, two of the three groups examined in our study had developed a particular expertise due to their specific training histories.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Cross-sectional studies comparing groups with different expertise levels have revealed that expertise is associated with beneficial functional brain network characteristics [25, 34, 35, 37]. In line with these findings, two of the three groups examined in our study had developed a particular expertise due to their specific training histories.…”
Section: Discussionsupporting
confidence: 82%
“…Experience-dependent alterations have been shown in resting state [63] as well as in task-related functional brain networks [34, 35, 37]. With regard to resting state, professional musicians showed increased functional connectivity in motor, visual, auditory, and somatosensory cortices [63].…”
Section: Discussionmentioning
confidence: 99%
“…For example, brain areas involved in performing an action were engaged more strongly during the perception of actions for which the observers have a specific motor expertise than for actions for which the participants only possess visual experience (e.g. dancers: Calvo-Merino, Grèzes, Glaser, Passingham, & Haggard, 2006; volleyball and tennis players: Balser et al, 2014;pianists: Haslinger et al, 2005;Haueisen & Knösche, 2001; biologically possible vs. impossible actions: Stevens, Fonlupt, Shiffrar, & Decety, 2000).…”
Section: Action Perception Across Life Span 3 !mentioning
confidence: 99%
“…These findings suggest that the processes related to sensory perception (e.g., visual system) and action (motor system) are tightly integrated during visual–perceptual–motor behaviour. In relation to anticipation in sport, several studies using neurophysiological measures such as fMRI with video‐based temporal occlusion have confirmed greater coactivation of sensory and motor regions of the brain in experts compared with less skilled players (e.g., Balser et al, ; Calvo‐Merino, Glaser, Grèzes, Passingham, & Haggard, ; Wright, Bishop, Jackson, & Abernethy, ).…”
Section: Psychological Theories Of Perceptual–motor Behaviourmentioning
confidence: 99%